2022
DOI: 10.3389/fonc.2021.667397
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Minimal Residual Disease to Prevent Late Recurrence in Hormone-Receptor Positive Breast Cancer: Challenges and New Approaches

Abstract: While the majority of breast cancers are diagnosed at a curable stage, approximately 20% of women will experience recurrence at a distant site during their lifetime. These metastatic recurrences are incurable with current therapeutic approaches. Over the past decade, the biologic mechanisms underlying these recurrences have been elucidated, establishing the existence of minimal residual disease in the form of circulating micrometastases and dormant disease, primarily in the bone marrow. Numerous technologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Given the potential of these scientific advances, plus the large unmet clinical need, the National Cancer Institute sponsored a Clinical Trials Planning Meeting in May 2019, from which evolved REFINE-BrCa (Refining Adjuvant Therapy Through Identification and Escalation), a collaboration across National Clinical Trials Network group members who are developing clinical trials to address these key questions about breast cancer late recurrence. 15…”
Section: Clinical Challenges In Evaluation and Treatmentmentioning
confidence: 99%
“…Given the potential of these scientific advances, plus the large unmet clinical need, the National Cancer Institute sponsored a Clinical Trials Planning Meeting in May 2019, from which evolved REFINE-BrCa (Refining Adjuvant Therapy Through Identification and Escalation), a collaboration across National Clinical Trials Network group members who are developing clinical trials to address these key questions about breast cancer late recurrence. 15…”
Section: Clinical Challenges In Evaluation and Treatmentmentioning
confidence: 99%
“…With an increasing body of evidence pointing to the possibility that MRD might identify and stratify patients' personal recurrence risk, a new generation of prospective studies is essential to address the critical gaps in our understanding. 13 Is the risk conferred by having detectable ctDNA without scan-confirmed measurable disease a modifiable risk? A simple first step is to determine whether lead time over radiographic metastatic disease exists through dedicated prospective studies since surveillance systemic imaging is not standard in breast cancer follow-up.…”
mentioning
confidence: 99%
“…Before there is a known effective intervention for MRD-positive patients without scan-detectable disease, MRD testing may contribute to unintentional harm if incorporated into routine clinical practice. 35 Our institution is studying patient understanding of and attitudes toward late recurrence in a survey study on Patient-reported Outcomes in Women with ER+/PR+ breast cancer (POWER). Additionally, many patients with early-stage HR+ breast cancer in the late adjuvant setting ultimately die of non–breast cancer causes including cardiovascular, cerebrovascular, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%